Anti-fibrosis effect for Hirsutella sinensis mycelium based on inhibition of mTOR p70S6K phosphorylation. Issue 7 (October 2017) - Yue, Huimin; Zhao, Yarong; Wang, Haining; Ma, Feiya; Liu, Fei; Shen, Sunan; Hou, Yayi; Dou, Huan
Hirsutella sinensis, cultured in vitro, is an attractive substitute for Cordyceps sinensis as health supplement. The aim of this study was to demonstrate whether H. sinensis mycelium (HSM) attenuates murine pulmonary fibrosis induced by bleomycin and to explore the underlying molecular mechanisms. Using lung fibrosis modle induced by intratracheal instillation of bleomycin (BLM; 4 mg/kg), we observed that the administration of HSM reduced HYP, TGF-β1 and the production of several pro-fibrosis cytokines (α-smooth muscle actin, fibronectin and vimentin) in fibrotic mice lung sections. Histopathological examination of lung tissues also demonstrated that HSM improved BLM-induced pathological damage. Concurrently, HSM supplementation markedly reduced the chemotaxis of alveolar macrophages and potently suppressed the expression of inflammatory cytokines. Also, HSM influenced Th1/Th2 and Th17/Treg imbalance and blocked the phosphorylation of mTOR pathway in vivo . Alveolar epithelial A549 cells acquired a mesenchymal phenotype and an increased expression of myofibroblast markers of differentiation (vimentin and fibronectin) after treatment with TGF-β1. HSM suppressed these markers and blocked the phosphorylation of mTOR pathway in vitro . The results provide evidence supporting the use of HSM in the intervention of pulmonary fibrosis and suggest that HSM is a potential therapeutic agent for lung fibrosis.